Monitoring and assessment of land degradation and desertification: towards new conceptual and integrated approaches - Vogt JV; Safriel U; Maltitz, G. von; Sokona Y; Zougmoré, Robert B.; Bastin, G.; Hill J (Wiley, 2011)
The implementation of the United Nations Convention to Combat Desertification (UNCCD) needs agreed, scientifically sound and practical methodologies for monitoring and assessing the state and trend of land degradation as well as for monitoring the performance of management programmes. The lack of sufficient and integrated monitoring and assessment (M&A) has in the past been identified as a major constraint for combating desertification. Implementing efficient M&A programmes, however, requires careful analysis of the information needs of the different stakeholders, a clear scientific concept of the processes and drivers of land degradation and an analysis of the theoretical and practical possibilities for adequate M&A. This paper briefly analyses the information needs of diverse stakeholders, reviews existing M&A systems, and highlights key aspects for a scientifically sound approach to monitoring and assessment. Analysis of existing approaches shows that in spite of their relevance, standardised procedures for their implementation at operational scales are lacking. This is partly attributable to the lack of agreed and clear definitions, related difficulties in defining and hence in measuring the attributes chosen to represent land degradation and desertification and the varying degrees of paucity of field data. There is also the urgent need to better integrate bio-physical and socio-economic aspects of desertification through a suitably robust scientific framework that links the drivers, processes and symptoms of desertification. Such a framework will allow for the identification of key variables to be monitored and will provide a basis for an improved forecasting and assessment of vulnerability, thereby providing highly important information for policy- and decision-making.